Multidrug-Resistant Bacteroides fragilis Bacteremia in a US Resident: An Emerging Challenge - Cristian Merchan; Sunita Parajuli; Justin Siegfried; Marco R. Scipione; Yanina Dubrovskaya; Joseph Rahimian (Case Reports in Infectious Diseases)
We describe a case of Bacteroides fragilis bacteremia associated with paraspinal and psoas abscesses in the United States. Resistance to b-lactam/b-lactamase inhibitors, carbapenems, and metronidazole was encountered despite having a recent travel history to India as the only possible risk factor for multidrug resistance. Microbiological cure was achieved with linezolid, moxifloxacin, and cefoxitin.